Pengaruh Pola Asuh Orang Tua Terhadap Children Well Being Anak Usia Dini - Wardiatul Aini; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Child well-being is a key indicator for assessing the quality of a child’s development from an early age. This encompasses not only physical health but also emotional, social, and psychological aspects that are shaped through interactions with the environment, particularly with the family. This study aims to analyze how parenting styles impact child well-being in early childhood. The method employed is a literature review examining various scientific references from the past ten years. The findings indicate that a nurturing, responsive, and balanced parenting approach can enhance child well-being, whereas parenting that is either overly strict or overly permissive risks hindering a child’s development. Consequently, the role of parents is crucial in fostering an environment that supports children’s development to the fullest extent